Pengaruh Foreign Debt, Liquidity dan Firm Size terhadap Hedging Decision (Studi Kasus Perusahaan Manufaktur Subsektor Semen Yang Terdaftar di BEI Tahun 2017-2023) - Febrianti, Berliana; Angelica Cindiyasari, Shiwi (DINASTI RESEARCH, 2024)
This study aims to analyze the influence of foreign debt, liquidity and firm size on hedging decisions in cement subsector manufacturing companies listed on the Indonesian stock exchange during the period 2017-2023. The sample of this study consisted of 6 companies with a total 42 observations. The method used in this study was a descriptive statistical analysis, classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination test (R2). The results show that foreign debt and liquidity do not have a significant influence on hedging decisions, while firm size has a significant influence on hedging decisions. Thisw, large companies in the cement subsector can leverage their size advantage in managing financial risk, while companies that are small may need to re-evaluate their risk management strategies. This study is expected to contribute to the development policies in the manufacturing sector, paticularly in the cement subsector.